Location of the Maltose A and B Loci on the Genetic Map of Escherichia coli - Schwartz, Maxime (1966)
Schwartz, Maxime (Institut Pasteur, Paris, France). Location of the maltose A and B loci on the genetic map of Escherichia coli. J. Bacteriol. 92:1083–1089. 1966.—All of the mutations impairing maltose metabolism that have been found in Escherichia coli map in one of the two loci, malA and malB. The position of malA in relation to the streptomycin, diaminopimelic acid + homoserine, and glycerol D loci were established both by sexual crosses and by P1 transduction. A new biotin marker was also shown to be located in this region. The position of malB was studied in relation to the loci for arginine F, methionine A, ultraviolet radiation A, and the origin of transfer of Hfr P10.